Indigenous Elite and Modern Democracy: Case Study of Legislator at Gowa Regency - Haslinda B Anriani; Ansar Arifin; Rasyidah Zainuddin (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract: This paper aims to reveal ’lunge’ indigenous elite that took place in a modern democratic society in Gowa, especially when the on going process of organizing elections out 2009. Some legislator selected 2009-2014 Gowa who had a background in traditional elite became evident how important power political bargaining in Gowa. Three of the members of parliament of the indigenous elite serve as the primary data source through in-depth interviews. The findings obtained are: indigenous elites who hav ea sound base large masses have strong political bargaining for gaining seats in parliament Gowa. Most of the indigenous elite who involved as a candidate does not have the capacity of education and political experience. Interestingly, they still dorationality political status attached to him.Keywords: Traditional Elite, Parliament, Legislators, Modern Democracy